A NEW EXTENSION OF THE FERRARI-IBANEZ COLLIDING WAVE SOLUTION - GURTUG, O (Plenum Publ Corp, 1995)
We show that for a specific choice of our seed function we obtain an interesting solution which reduces to the well-known solutions of Khan-Penrose, Bell-Szekeres and Ferrari-Ibanez-Griffiths in particular limits. We also present a solution that describes the collision of gravitational quadrupoles.
Keywords: Gravitational Plane-Waves; Einstein-Maxwell Theory; Large Family